Advanced Methods and New Materials for Cultural Heritage Preservation - Turcanu-Carutiu, Daniela; Ion, Rodica-Mariana (IntechOpen, 2019)
The integration of science with art is a complex process of analysis and the knowledge and understanding of the need to save and protect works of art as well as preserve and restore cultural heritage. This is generally provoked by the living necessity, profoundly human, to leave our inheritance to new generations, as intact as is possible, the testimonies of the past.The issues approached interfere with artistic criticism, for example, biological and physico-chemical analyses, and intelligent mathematical modeling systems such as Marker-less Augmented Reality, 3D Reconstruction, intelligent combinations of digital image analysis functions to recognize and estimate the possible evolution of color and shape to help experts make the best decisions about authenticating and preserving-restoring art objects.Advanced technical devices such as digital databases and other tools and materials can allow for the eradication of offenses such as false art and falsification.